Pengaruh Ekstrak Biji Ketapang (Terminalia catappa L.) Terhadap Daya Hambat Pertumbuhan Bakteri Eschericia coli: Effect of Ketapang (Terminalia catappa L.) Seed Extract Against the Inhibitory Power of Eschericia coli Bacteria Growth - Zelen Surya Minata Minata; Annida Elfiana Citra Ardianty; Sumari; Yudhi Utomo (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Diarrheal is a disease that is widely endemic in tropical countries, especially in Indonesia. The bacterium that causes the appearance of diarrheal diseases is Eschericia coli. Plants that have the potential to be a cure for diarrhea are ketapang (Terminalia catappa L.). Ketapang seeds contain tannins, flavonoids, alkaloids, and saponins that can be used as antibacterial. This study aims to identify the effect of ketapang seed extract on the activity of E. coli bacteria. Extraction of ketapang seeds is carried out by the soxhlet extraction method with a solvent mixture of water and ethanol 96%. This research is a laboratory experiment. Bacterial growth inhibition test is carried out by the phytochemical test of ketapang seed extract with the addition of FeCl3 solution showed positive results containing tannin compound indicated by the formation of a blackish-green colored solution. Positive control was carried out with amoxicillin and negative control with 70% ethanol solution. The results of the ANOVA test analysis obtained a significance value of 0.963, interpreted that there was a difference in inhibition power in variations in the concentration of ketapang seed extract with the most effective extract concentration being 0.8%. The higher the concentration of ketapang seed extract, the greater the inhibition against the growth of E. coli bacteria, therefore it can be used as a basic ingredient for anti-diarrhea drugs.